Anti-Self Accusations Among Psychologically Abused Middle School Students (Journal of the College of Basic Education, 2024)
The current research aims to identify the level of anti-self-accusations of psychologically abused female middle school students. The current research is limited to psychologically abused female students (middle school students). The current research population was (4185) female students from the second middle school stage in Al-Muqdadiyah District and Khanaqin District, affiliated with the General Directorate of Education. Diyala for the academic year (2023-2024), for the purpose of conducting statistical analysis of the anti-self-accusations scale, the researchers chose a sample consisting of (400) female students from the middle school, and after processing the data using the SPSS statistical package, the research reached the following results, and the results indicate that the female students included in the current research They have a high degree of self-accusation. Statistical analysis of the results of applying the anti-self-accusations scale showed that psychologically violent female students have accusations directed at themselves because of the burdens and difficulties of life. This may lead to the creation of psychological conditions, situations of conflict, and negative emotions resulting from a feeling of helplessness, weakness, and contradiction between life. Reality and ambition, and the research came out with a set of recommendations, the most important of which are: using the anti-self-accusations scale in psychological centers due to its ability to give indicators of the level of feelings of anti-self-accusations, developing awareness programs and psychological guidance for those who suffer from anti-self-accusations, and staying away from methods of constant blaming and reprimanding for the simplest mistakes. And work to follow up on the students’ problems and find out what psychological pressures they are suffering from, and work to reduce their effects through joint cooperation between the educational counselor and the students.